Quality And Potential Of Rambutan Peel (Nephelium Lappaceum L.) Kombucha As A Health Drink - Ismedsyah Ismedsyah; Lavinur Lavinur (International Journal Labs, 2025)
Herbal infusion in the form of tea skin fruit rambutan can consumed as drink healthy home . Aside from made into drink home , tea skin fruit rambutan Can Also changed into other processed drinks such as kombucha drink . To produce a quality kombucha drink with health potential, several chemical characteristics need to be determined. The purpose of the study was to study the effect of variations in sugar concentration and fermentation time on chemical characteristics. Design Which used on study This is design random group (RACK) with One factor namely long day fermentation Which consists of from 3 level as following : L 1 = long fermentation 1 0 day , L 2 = long fermentation 1 2 day , L 3 = long fermentation 14 day , with each foreign m treatment repeated as many as 3 times so that obtained 9 unit study . And variation concentration sugar G1 = 5%, G2 = 10%, G3 = 15% . The results of the study of variations in sugar concentration and fermentation time of rambutan fruit skin kombucha affect the total acidity, vitamin C levels, pH and organoleptic properties so that it is likely good as a health drink. Variations concentration sugar and fermentation time influence total acid content , vitamin C, pH, organoleptic drink Kombucha skin fruit rambutan and is best at a sugar concentration of 15% and a fermentation period of 14 days.